In fibonacci sequence each item is the sum of the previous two. So, you wrote a recursive algorithm.
So,
fibonacci(5) = fibonacci(4) + fibonacci(3) fibonacci(3) = fibonacci(2) + fibonacci(1) fibonacci(4) = fibonacci(3) + fibonacci(2) fibonacci(2) = fibonacci(1) + fibonacci(0)
Now you already know fibonacci(1)==1 and fibonacci(0) == 0. So, you can subsequently calculate the other values.
Now,
fibonacci(2) = 1+0 = 1 fibonacci(3) = 1+1 = 2 fibonacci(4) = 2+1 = 3 fibonacci(5) = 3+2 = 5
And from fibonacci sequence 0,1,1,2,3,5,8,13,21…. we can see that for 5th element the fibonacci sequence returns 5.
like in your code
int a = 0; int fib = 1; for(int i=0; i<5; i++) { fib = fib + a; a = fib; } return fib; //5
This returns 4 for fibbonnacci(3):
i=0;fib=1;a=0 so: {fib= fib+a => fib==1;a= fib => a==1} (first iteration)
i=1;fib=1;a=1 so: {fib= fib+a => fib==2;a= fib => a==2} (second iteration)
i=2;fib=2;a=2 so: {fib= fib+a => fib==4;a= fib => a==4} (third iteration)